2011
DOI: 10.1016/j.jpainsymman.2010.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Experiences of Belgian Physicians Regarding Euthanasia Practice and the Euthanasia Law

Abstract: Most physicians studied support euthanasia for terminal patients with extreme uncontrollable pain/symptoms and agree that euthanasia can be part of good end-of-life care. Although physicians had little involvement in the process of legalizing euthanasia, they now generally endorse the euthanasia law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 20 publications
(18 reference statements)
0
49
0
6
Order By: Relevance
“…A survey conducted in Belgium, where euthanasia is legal, found that 90.4% of the 914 participating physicians agreed to practice euthanasia for patients of terminal disease involving uncontrollable pain or other extreme suffering 13 , showing the existing difference in perception.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in Belgium, where euthanasia is legal, found that 90.4% of the 914 participating physicians agreed to practice euthanasia for patients of terminal disease involving uncontrollable pain or other extreme suffering 13 , showing the existing difference in perception.…”
Section: Discussionmentioning
confidence: 99%
“…The relative underrepresentation of reported euthanasia cases from the French-speaking community and the differences in case characteristics corroborate previous studies that found significant differences between Flanders and Wallonia in terms of practice, attitudes and knowledge about euthanasia. [10][11][12]14 These differences suggest that euthanasia legislation does not have a predetermined effect on medical end-of-life practice and that social and cultural elements also influence its development.…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies have found differences in end-of-life practices, knowledge and attitudes between the regions and language communities, showing that Dutchspeaking physicians more often receive and grant euthanasia requests and are more inclined to adhere to legal safeguards. [10][11][12][13][14] The reports issued by the Federal Control and Evaluation Committee on Euthanasia show a striking disparity in euthanasia reporting between the 2 language communities. [4][5][6][7][8][9] Trends in the characteristics of reported cases and differences among them have not yet been studied.…”
mentioning
confidence: 99%
“…Besides, there was a significant relation between the second (If you agree with the death penalty, which one is more suitable, painless or painful) and fourth (If you agree with euthanasia, which one is more suitable, active or passive) warm-up questions, determining kinds of punishment and euthanasia pertaining to legal or medical scenarios, respectively (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%